2022
DOI: 10.1101/2022.03.09.483616
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell-surface PD-L1 expression identifies a sub-population of distal epithelial cells enriched in idiopathic pulmonary fibrosis

Abstract: Idiopathic lung fibrosis (IPF) is a fatal lung disease characterized by chronic epithelial injury and exhausted repair capacity of the alveolar compartment, associated with the expansion of cells with intermediate alveolar epithelial cell (AT2) characteristics. Using SftpcCreERT2/+: tdTomatoflox/flox mice, we previously identified a lung population of quiescent injury activated alveolar epithelial progenitors (IAAPs) marked by low expression of the AT2 lineage trace marker tdTomato (Tomlow), and characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…How IAAPs responded to FGFR2b signaling and escaped Fgfr2b deletion remains to be further investigated. Our most recent study further identified the human equivalent of the IAAPs, which were amplified in IPF patients [ 27 ]. These findings are consistent with our initial description of this newly identified AT2 subpopulation as becoming activated and proliferative in the context of PNX-induced injury [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…How IAAPs responded to FGFR2b signaling and escaped Fgfr2b deletion remains to be further investigated. Our most recent study further identified the human equivalent of the IAAPs, which were amplified in IPF patients [ 27 ]. These findings are consistent with our initial description of this newly identified AT2 subpopulation as becoming activated and proliferative in the context of PNX-induced injury [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A puzzling question related to the behavior of IAAPs in end-stage IPF is their lack of contribution to the mature AT2 lineage. These cells are indeed amplified in IPF but seem to be stalled in their differentiation status [ 27 ]. One possibility explaining this failure to differentiate could be linked to the high inflammatory status of these lungs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations